Cultural values of ecosystem services from coastal marine areas: Case of Taytay Bay, Palawan, Philippines. Issue 142 (April 2023) - Gajardo, Lea Janine; Sumeldan, Joel; Sajorne, Recca; Madarcos, John Roderick; Goh, Hong Ching; Culhane, Fiona; Langmead, Olivia; Creencia, Lota
Abstract: The Philippine coastal marine ecosystem provides many Ecosystem Services (ES) and is a region where coastal communities are closely dependent on the sea. Previous ES studies focus mainly on biophysical and economic assessments with limited studies about Cultural Ecosystem Services (CES), particularly in the Philippines. Here, we present the CES provided by Taytay Bay, Palawan through local knowledge. Using semi-structured interviews together with participatory mapping activities we quantified marine-related values and threats across Taytay Bay. Spatial mapping of CES, including sense of place, heritage, identity, spiritual, inspiration, knowledge, education, aesthetics, recreation, and intergenerational showed benefits occurring in particular spatial patterns, suggesting that services are provided and contribute to human wellbeing at a community level. Respondents highly valued benefits to their livelihoods but also identified many distinct values beyond income generation, including sense of place, spiritual, aesthetics, and recreational values. The connection between some cultural services e.g., source of ecological knowledge, and provisioning services e.g., seafood, was also recognized. Destructive fishing practices, agrochemicals from pearl and seaweed farms, and privatization of islands were perceived to introduce the highest threats. This has management implications since threats to CES also threaten other ES. The co-occurrence of CES values with provisioning values suggests a holistic approach to ecosystem valuation is needed. The loss of one ES is likely to represent a loss in multiple other services and protecting key service-providing habitats leads to multiple benefits. The study results demonstrate the importance of integrating cultural and non-monetary environmental values into ecosystem valuation and practical on-the-ground policies. Highlights: First study on cultural services from coastal marine areas in Palawan, Philippines. Cultural ecosystem services valuation based on local perception. Interlinking ecosystem services. Low values on cultural services within formal education system. Anthropogenic factors threatening the capacity of the coastal marine environment to provide ecosystem services.